The Urgency Improvement Financial literacy (accounting) to improve competitiveness of Micro, Small, and Medium Enterprises (SME) based on local wisdom - Sri Setiti; Maulana Rizky; Khalfia Khairina (AIBPM Publisher, 2019)
This paper aims to illustrate the understanding of Micro Small Medium Enterprises (SME) actors based on local wisdom on the preparation of financial statements for access to financing. At present, the Indonesian Institute of Accountants (IAI) has implemented a regulation on Micro, Small and Medium Enterprises (SME) Financial Accounting Standards effective January 1, 2018 to facilitate SME access to Banking Services. UKM-based local wisdom which is the object of research is a micro business that produces sago stems into wet sago. The method used in this research is descriptive qualitative. The type of data used in this study is the primary data obtained through interviews of micro business actors that produce sago stems into sago wet in the Village of Pemakuan Banjar. Business actors producing sago trunks become wet sago characteristic of the area, but the field still can not develop for the better because of limited access to banking. The results of the study illustrate that micro business actors in the village of pemakuan not have an understanding of the preparation of financial statements. SME business actors in the village of pemakuan did not record the buying and selling process. The SME actor considers that it is difficult to conduct bookkeeping such as recording sales and purchases, then low levels of education greatly affect the assessment of the importance of recording financial activities. The Financial Accounting Standards of Micro, Small and Medium Enterprises (SME) which will be effective on 1 January 2018 will be difficult to be applied by micro, small and medium business actors that have been approved by the Indonesian Institute of Accountants.